The Electromagnetic potential gradient ,Ca2+ and Starch-Statoliths on the Uneven Growth of Plants - PSB Wanduragala; JP Eeswara; WAJM De Costa (Tropical Agricultural Research, 2011)
Effect of electromagnetic potential gradients on the uneven growth of shoot apex of Phaseolus vulgaris was investigated. Phaseolus vulgaris plants were fixed to a 3 - D clinostat with microelectrodes which applied an electromagnetic potential gradient (E.M.P.G.). The effect of gravity on the plant fixed to the 3-D clinostat was eliminated by rotating the plant at 1-resolution per minute (rpm). The applied E.M.P.G. was noted to replace gravity. This denotes that the gravity signal felt by the plant may be transuded through E.M.P.G. From the experiments carried-out, Calcium ions (Ca2+) and starchstatoliths were rejected as signal perceptors. Results proved that there was a trophic movement even when Ca2+ ions were blocked in travelling un-evenly by an inhibitor EDTA. At the same time, roots which did not have starch-statoliths showed response to gravity. These results indicate that the gravity signal could be replaced with an E.M.P.G. and at the same time it is neither Ca2+ ions nor starch –statoliths that perceive the gravity signal. Thus, it may be possible that the physical stimuli are transferred to a biological signal through an E.M.P.G. Abbreviations: 3-D – three dimensional, E.M.P.G.-Electromagnetic potential gradient DOI: http://dx.doi.org/10.4038/tar.v21i3.3308 TAR 2010; 21(3): 321-326